Assessment of modulus using falling weight deflectometer and cores for stabilized layer. (2020) - Singh, Gaurav; Jain, Sunil; Tiwari, Devesh; Dave, S.M.; Singh, Ajaypal
Abstract: There are conventional methods available for designing of flexible pavement based on the past experience whereas for the design of Cement Treated Base (CTB) and Cement Treated Sub Base (CTSB) layers no such conventional methods are available. Use of cement stabilization in granular material is an effective technique to increase the stiffness of base and sub base layers and also in the thickness reduction in comparison to conventional layers. Furthermore, cement base layers can improve the fatigue behaviour of asphalt surface layer and subgrade rutting over the short and long term. In our country, there is no performance data available for CTB and CTSB layers in in-situ conditions. This paper deals with the investigation of the resilient modulus (MR ) of stabilized pavement layers through field data collection on in-service flexible pavement sections which may be useful for design purpose. The main objective of this research study is to make a comparison of MR values for cement stabilized layers using non-destructive method viz. Falling Weight Deflectometer (FWD) and destructives test method through cores. The field data has been collected from State Highway (SH) and Major District Road (MDR) around Lucknow, Uttar Pradesh. No visual distress was observed on both the road sections at the time of field surveys. Two study sections on SH and one on MDR of about 500 m length has been identified for the study. The in-situ cores were obtained from CTB and CTSB layers which were tested for determination of MR values through Unconfined Compressive Strength (UCS) as per IRC:37-2018. FWD deflection data was used for determination of MR values using backcalculation software for CTB and CTSB layers. Furthermore, the thickness and the properties of each layer were determined by conducting test pits on the existing pavement.